2016
DOI: 10.4317/jced.52923
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of oral health in paediatric patients with disabilities: Sensory disorders and autism spectrum disorder. Systematic review II

Abstract: IntroductionWe are currently witnessing an increase in the number of disabled patients, creating the need for knowledge of each of the pathologies and of the different oral and dental conditions they present, in order to achieve efficient management and treatment.ObjectivesTo analyse the existing scientific literature on the oral conditions of children with autism spectrum disorder (ASD) and children with sensory deficits (SD), in comparison with the healthy child population.Material and MethodsThe bibliograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 15 publications
0
48
0
4
Order By: Relevance
“…It is well demonstrated that oral hygiene causes problems with aesthetics and communication, with solid biological, psychological, and social implications (Emami, de Souza, Kabawat, & Feine, ). Sadly, oral health care ranks among the most ignored health needs of disabled individuals (Bartolome‐Villar, Mourelle‐Martinez, Dieguez‐Perez, & de Nova‐Garcia, ; Dieguez‐Perez, de Nova‐Garcia, Mourelle‐Martinez, & Bartolome‐Villar, ; Roberts, Chetty, Kimmie‐Dhansay, Fieggen, & Stephen, ). Oral health of the disabled could be overlooked due to either the disabilities themselves or more likely to their restricted access to oral health care (Dieguez‐Perez, et al, ; Roberts, et al, ; Jaber, Sayyab, & Abu Fanas, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well demonstrated that oral hygiene causes problems with aesthetics and communication, with solid biological, psychological, and social implications (Emami, de Souza, Kabawat, & Feine, ). Sadly, oral health care ranks among the most ignored health needs of disabled individuals (Bartolome‐Villar, Mourelle‐Martinez, Dieguez‐Perez, & de Nova‐Garcia, ; Dieguez‐Perez, de Nova‐Garcia, Mourelle‐Martinez, & Bartolome‐Villar, ; Roberts, Chetty, Kimmie‐Dhansay, Fieggen, & Stephen, ). Oral health of the disabled could be overlooked due to either the disabilities themselves or more likely to their restricted access to oral health care (Dieguez‐Perez, et al, ; Roberts, et al, ; Jaber, Sayyab, & Abu Fanas, ).…”
Section: Introductionmentioning
confidence: 99%
“…Estas técnicas deben ser individualizadas, teniendo en cuenta no sólo el trastorno del paciente, sino también su nivel, para tener una idea del grado de cooperación a obtener. Además, debemos analizar la patología oral del paciente, ya que la posibilidad de tratamientos largos o complejos nos puede ayudar a seleccionar la técnica más recomendable (Bartolomé-Villar et al, 2016).…”
Section: Introductionunclassified
“…These studies found that ASD children tend to have low levels of oral hygiene with an elevated plaque index as well as poor gingival and periodontal conditions. [9][10][11] Oral hygiene is the most influential risk indicator associated with the occurrence of new caries and lesions in children with ASD. 12 Consequently, their prevalence among ASDafflicted children is higher than in those without ASD, although the difference is not significant.…”
mentioning
confidence: 99%
“…12 Consequently, their prevalence among ASDafflicted children is higher than in those without ASD, although the difference is not significant. 10,11 Moreover, there is also an increase in the incidence of malocclusion, as well as parafunction or self-harming habits in children with ASD. 10 Various approaches and methods should be attempted to render such children co-operative during dental care procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation